The Downregulation of eIF3a Contributes to Vemurafenib Resistance in Melanoma by Activating ERK via PPP2R1B - Jiang, Shi-Long; Wang, Zhi-Bin; Zhu, Tao; Jiang, Ting; Fei, Jiang-Feng; Liu, Chong; Luo, Chao; Cheng, Yan; Liu, Zhao-Qian (Frontiers in Pharmacology, 2021)
Vemurafenib, a BRAF V600E inhibitor, provides therapeutic benefits for melanoma patients, but the frequently emergence of drug resistance remains a challenge. Understanding the mechanisms behind vemurafenib resistance may generate novel therapeutic strategy for melanoma patients. Here, we demonstrated that eIF3a, a translational regulatory protein, was an important mediator involved in vemurafenib resistance. EIF3a expression was significantly lower in vemurafenib-resistant A375 melanoma cells (A375R) compared with the parental A375 cells. Overexpression of eIF3a enhanced the sensitivity of BRAF inhibitor by downregulating p-ERK expression. We further revealed that eIF3a controls ERK activity though regulating the phosphatase PPP2R1B expression via translation mechanism, thus determining the sensitivity of vemurafenib in melanoma cells. In addition, the positive correlation between eIF3a and PPP2R1B was also demonstrated in tumor samples from HPA and TCGA database. In conclusion, our studies unveil a previously unknown molecular mechanism of BRAF inhibitors resistance, which may provide new strategy for predicting vemurafenib responses in clinical treatment.